Phytoassessment of Vetiver grass enhanced with EDTA soil amendment grown in single and mixed heavy metal–contaminated soil - Ng, Chuck Chuan; Boyce, Amru Nasrulhaq; Abas, Mhd Radzi; Mahmood, Noor Zalina; Han, Fengxiang (Springer, 2019)
Over the years, ethylene-diamine-tetra-acetate (EDTA) has been widely used for many purposes. However, there are inadequate phytoassessment studies conducted using EDTA in Vetiver grass. Hence, this study evaluates the phytoassessment (growth performance, accumulation trends, and proficiency of metal uptake) of Vetiver grass, Vetiveria zizanioides (Linn.) Nash in both single and mixed heavy metal (Cd, Pb, Cu, and Zn)—disodium EDTA-enhanced contaminated soil. The plant growth, metal accumulation, and overall efficiency of metal uptake by different plant parts (lower root, upper root, lower tiller, and upper tiller) were thoroughly examined. The relative growth performance, metal tolerance, and phytoassessment of heavy metal in roots and tillers of Vetiver grass were examined. Metals in plants were measured using the flame atomic absorption spectrometry (F-AAS) after acid digestion. The root-tiller (R/T) ratio, biological concentration factor (BCF), biological accumulation coefficient (BAC), tolerance index (TI), translocation factor (TF), and metal uptake efficacy were used to estimate the potential of metal accumulation and translocation in Vetiver grass. All accumulation of heavy metals were significantly higher (p < 0.05) in both lower and upper roots and tillers of Vetiver grass for Cd + Pb + Cu + Zn + EDTA treatments as compared with the control. The single Zn + EDTA treatment accumulated the highest overall total amount of Zn (8068 ± 407 mg/kg) while the highest accumulation for Cu (1977 ± 293 mg/kg) and Pb (1096 ± 75 mg/kg) were recorded in the mixed Cd + Pb + Cu + Zn + EDTA treatment, respectively. Generally, the overall heavy metal accumulation trends of Vetiver grass were in the order of Zn >>> Cu > Pb >> Cd for all treatments. Furthermore, both upper roots and tillers of Vetiver grass recorded high tendency of accumulation for appreciably greater amounts of all heavy metals, regardless of single and/or mixed metal treatments. Thus, Vetiver grass can be recommended as a potential phytoextractor for all types of heavy metals, whereby its tillers will act as the sink for heavy metal accumulation in the presence of EDTA for all treatments. © 2019, Springer Nature Switzerland AG.